Method for Developing a Side Impact Upper Neck Injury Criteria Which Compensates for Biomechanical Differences Between ATDs and Humans. Issue 2 (3rd April 2018) - Satava II, Stephen J.; Parr, Lt Col Jeffrey C.; Miller, Michael E.
OCCUPATIONAL APPLICATIONS: We developed a method to convert between the upper-neck lateral impact accelerative responses obtained from a human and an anthropometric test device (ATD). This conversion allows developers to employ cost-effective methods for applying human-derived neck injury criteria to testing in accelerative environments utilizing ATDs while accurately compensating for biofidelic shortcomings of existing ATDs. This compensation allows accurate risk determinations to be made early in the development cycle for crash systems, including fighter aircraft helmets and ejection seats.